Ensino Superior de Administração conectado às demandas do século XXI: inovação pedagógica é possível? - Silva, Ana Valéria Barbosa da (2022)
This research relates the current curricular structure of Business Administration programs and the characteristics required by the existing context for these professionals, identifying indicators on the potential for pedagogical innovation in the development of curricula. It was sought to understand what has been and what needs to be done in the development of curricula so that academic training is linked to the skills and abilities required by the organizational environment. This study pursued to achieve the following specific objectives: (i) identify the curricula components and the respective pedagogical practices through the analysis of political-pedagogical projects of Business Administration programs of selected Higher Education Institutions (HEIs). (ii) to infer the competencies and skills most preferred by organizations in the selection and hiring of business professionals. (iii) to build indicators of pedagogical innovation based on research carried out through bibliographic, surveys, document analysis, questionnaires, and interviews. The justification is based on the fact that organizational environments are challenging as a result of new paradigms, technological advances and complex societies which are constantly transformation. This scenario requires changes in the form and contents to be taught by HEIs to mitigate the mismatch between what the market is looking for in hiring professionals and what the courses offer. Educators have been proposing new look at classrooms and at the relationships between faculty and students with the aim of overcoming the current challenges of society in an environment of search for for pedagogical innovation and meaningful learning. This qualitative of a descriptive nature research is based on four-pillar. Systematic reviews of the literature were carried out, augmented by other bibliographic research on significant topics for the study’s foundation, building the research corpus. Documental research was carried out through an exploratory and descriptive analysis to map the pedagogical projects of nine selected business administration programs according to pre-established criteria. The third pillar was accomplished through an electronic questionnaire applied to recruiters and managers who hire administrators to identify the skills and abilities needed for managers in the current context. The fourth pillar consisted of semi-structured interviews with coordinators of business administration programs. Thus, the analysis of data obtained through the different sources was put together to respond to the objectives of the research. The theoretical framework brings together specialists in the field of Education. As main conclusions and contributions, the main soft skills desired by organizations were identified, and mapped as indicators of pedagogical innovation the construction of exchanged curricula that dialogue with companies and society in general. These curricula can promote training that connect theory and practice, establishing networks and enabling the renewal of higher education in Administration knoweldege field.This research is part of the Graduate Program in Education: Curriculum of PUC-SP, New Technologies in Education line of research, under the guidance of Prof. Dr. Maria Elizabeth Almeida